TRAINING ON MAKING DISH SOAP FOR IRT IN WEST PAYA ITEK VILLAGE, MEURAH MULIA DISTRICT - Muslina; Maulina, Isra; Haris Fajar Fahdillah; Ayu Lian Dari; Shofia Marwa Marpaung; Julitha Indah Nahdiyah Sibuea5; Sharah; Aminah; Sufrizal; Asra (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2024)
Laundry soap is an important product that cannot be separated from the activities of housewives in home care activities. On the other hand, the high demand is not comparable to the income level of the people in Gampong Barat Paya Iteuk who have lost their source of income because the rice fields are not being used. This prompted a team consisting of lecturers and six students to conduct training in making dishwashing soap. This activity has been implemented well and has invited positive responses from the training participants, namely housewives. Most participants want further education to develop entrepreneurial skills.